Multiple scale investigation of molecular diffusion inside functionalized porous hosts using a combination of magnetic resonance methods1. Issue 24 (28th June 2015) - Wessig, Martin; Spitzbarth, Martin; Drescher, Malte; Winter, Rainer; Polarz, Sebastian
<x xml:space="preserve">Abstract</x> Diffusion in organo-functionalized porous hosts could be tracked by evaluation of spin exchange processes using EPR spectroscopy.